Visualisation and quantification of morphogen gradient formation in the zebrafish. - Steven A Harvey (Public Library of Science (PLoS), 2009)
During embryonic development, signalling molecules known as morphogens act in a concentration-dependent manner to provide positional information to responding tissues. In the early zebrafish embryo, graded signalling by members of the nodal family induces the formation of mesoderm and endoderm, thereby patterning the embryo into three germ layers. Nodal signalling has also been implicated in the establishment of the dorso-ventral axis of the embryo. Although one can infer the existence of nodal gradients by comparing gene expression patterns in wild-type embryos and embryos in which nodal signalling is diminished or augmented, real understanding can only come from directly observing the gradients. One approach is to determine local ligand concentrations in the embryo, but this is technically challenging, and the presence of inhibitors might cause the effective concentration of a ligand to differ from its actual concentration. We have therefore taken two approaches to visualise a direct response to nodal signalling. In the first, we have used transgenic embryos to study the nuclear accumulation of a Smad2-Venus fusion protein, and in the second we have used bimolecular fluorescence complementation to visualise the formation of a complex between Smad2 and Smad4. This has allowed us to visualise, in living embryos, the formation of a graded distribution of nodal signalling activity. We have quantified the formation of the gradient in time and space, and our results not only confirm that nodal signalling patterns the embryo into three germ layers, but also shed light on its role in patterning the dorso-ventral axis and highlight unexpected complexities of mesodermal patterning.